FACTORS FOR CHANGES IN TRADING VOLUME, CHANGES IN MARKET CAPITALIZATION, AND CHANGES IN CIRCULATING SUPPLY TO BINANCE COIN (BNB) RETURNS - Denny Adi Nugroho; Rahmat Setiawan (Jurnal Ekonomi, 2023)
This study aims to analyze the effect of changes in trading volume, changes in market capitalization, and changes in circulating supply on binance coin returns. The variables studied are independent variables, changes in trading volume, changes in market capitalization, changes in circulating supply and the dependent variable, namely binance coin returns. Binance coin research sample for the period 2019 – 2021. The data used in this research is monthly secondary data obtained through the coinmarketcap.com website. The data is processed using the Multiple Linear Regression method to determine the effect of independent variables on binance coin returns. The results of the study show that: 1) The variable change in trading volume has no significant effect on binance coin returns; 2) Variable changes in market capitalization have a significant positive effect on binance coin returns; 3) Variable changes in circulating supply have a significant negative effect on binance coin returns.